The Molecular Genetics of Lung Cancer - Cooper, David N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Lung cancer is the leading cause of cancer mortality in Western countries. It also provides an archetypal example of how inherited predisposing genetic variants may interact with an environmental influence (smoking) to modulate individual cancer risk. The Molecular Genetics of Lung Cancer describes how the new techniques, methods and approaches of molecular genetics are being used to unravel the complexities of the mechanisms underlying lung tumorigenesis by analysis at the DNA, RNA and protein levels with potentially important implications for tumour classification, diagnosis, prognosis and treatment as well as providing new insights into how lung tumours arise and how they progress to malignancy.
An Introduction to the Molecular Basis of Cancer -- Lung Cancer: Setting the Scene -- Genes Involved in Sporadic Forms of Lung Cancer -- Somatic Mutation in Lung Cancer -- Genetic Approaches to Studying the Association Between Smoking and Lung Cancer -- Evidence for Genetic Susceptibility to Lung Cancer Derived from Polymorphism-disease Association Studies -- Gene Expression Studies in Lung Cancer -- Lung Cancer Pathogenesis and Future Prospects for Treatment and Prevention.
Keywords: Cancer research; Oncology .; Human genetics; Cancer Research; Oncology; Human Genetics